New record of Rhynobrissus cuneus Cooke, 1957 (Echinoidea, Spatangoida) from the eastern Florida coast - Angela D. Witmer; Rich Mooi (Check List)
The Brissidae is a family of heart urchins that includes shallow‑water, infaunal species, some of which are rarely observed. One species, Rhynobrissus cuneus Cooke, 1957, has only been recorded from the western Atlantic off the coast of North Carolina, USA and in the Gulf of Mexico off the coast of Veracruz, Mexico. This work identifies new records from the coast of Florida, USA, increasing our knowledge of this species’ geographic distribution.